2013
DOI: 10.1111/imm.12125
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a specific haptoglobin C‐terminal fragment in arthritic synovial fluid and its effect on interleukin‐6 expression

Abstract: SummaryHaptoglobin (Hp), a major acute-phase plasma protein, has been found in arthritic synovial fluid (SF). However, the function and structural modifications of Hp in arthritic SF are unknown. To investigate in vivo generation of modified Hp associated with inflammatory disease, we examined a new Hp isoform in SF from patients with rheumatoid arthritis (RA). Specific Hp fragments of 28 000 and 15 000 molecular weight were identified in SF of patients with RA, and the two polypeptides were presumed to be fra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…While haptoglobin is typically anti-inflammatory, glycosylation site alterations have been identified in RA and other diseases such as cancer; the ability of glycosylation to alter protein function and immunogenicity suggests that glycosylation alterations may serve pathogenic roles [ 28 30 ]. In RA synovial fluid, a specific haptoglobin isoform upregulates monocyte IL-6 production [ 31 ]. Also, synthesis of haptoglobin is primarily hepatic; however, it is also produced by activated neutrophils and taken up peripherally by monocytes [ 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While haptoglobin is typically anti-inflammatory, glycosylation site alterations have been identified in RA and other diseases such as cancer; the ability of glycosylation to alter protein function and immunogenicity suggests that glycosylation alterations may serve pathogenic roles [ 28 30 ]. In RA synovial fluid, a specific haptoglobin isoform upregulates monocyte IL-6 production [ 31 ]. Also, synthesis of haptoglobin is primarily hepatic; however, it is also produced by activated neutrophils and taken up peripherally by monocytes [ 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Also, synthesis of haptoglobin is primarily hepatic; however, it is also produced by activated neutrophils and taken up peripherally by monocytes [ 32 , 33 ]. Thus, the source, balance, and functions of haptoglobin and other acute phase proteins in RA are different from those in healthy controls and likely contribute to different GlycA associations [ 31 ]. Although we did not assess the individual acute phase protein contributions to GlycA in this sample, we suggest that GlycA is a comprehensive measure of pathogenic inflammation in RA.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, haptoglobin was found to be a monocyte chemoattractant whose chemotactic potential was mediated, at least in part, by its interaction with chemokine (C-C motif) receptor 2 [ 20 ]. Recently, Park and co-workers demonstrated that the C-terminal haptoglobin fragment is generated by plasmin in local inflammatory environments, suggesting that this fragment might be applied as a novel biomarker for the diagnosis and prognosis of inflammatory joint diseases such as rheumatoid arthritis [ 21 ]. Hemopexin belongs to the acute phase reactants, the synthesis of which is induced after inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…These conflicting findings may be due to the diverse functions of Hp isoforms produced in various cellular environments. In fact, we recently identified a specific Hp fragment in the synovial fluid of patients with rheumatoid arthritis that appears to be produced by plasmin and induces IL-6 expression [24]. Because of different processing and post-translational modifications, such as glycosylation and protease cleavage, diverse Hp isoforms may be generated in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…COS‐7 CM and serum proteins were separated on a 10% SDS–polyacrylamide gel, and Hp isoforms were identified using anti‐human Hp antibody (Sigma–Aldrich) and polyclonal antibodies against human Hp α‐chain and Hp β‐chain, which were prepared from rabbit sera after immunization against the corresponding recombinant protein [24]. The immunoreactive proteins were detected using an enhanced chemiluminescence detection kit (Amersham Biosciences, Buckinghamshire, UK) and luminescent image analysis LAS‐3000 system (Fujifilm, Tokyo, Japan).…”
Section: Methodsmentioning
confidence: 99%